Pengaruh Rasio Profitabilitas, Likuiditas, dan Aktivitas Terhadap Nilai Perusahaan Sektor Non-Cyclicals Periode 2021-2024 - Veren, Veren; Susanti, Merry (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The problem in this study is related to the impact of the pandemic and post-pandemic periods, which led to restrictions on economic activities and hindered business growth in the consumer non-cyclical sector, a sector known for its relative stability. This study aims to analyze the effect of profitability, liquidity, and total asset turnover on firm value in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. This study was processed using IBM SPSS Statistics Version 31, with a sample of 308 data from 77 consumer non-cyclicals companies. However, 142 out of 308 company data were identified as outliers and did not fulfill the normality test in the classical assumption test, resulting in 166 samples used in this study. This study used Tobin’s Q as a parameter in measuring firm value. Data analysis methods used were classical assumption tests, descriptive statistics, coefficient of multiple determination, t-tests, F-tests, and multiple linear regression analysis. Based on the research results, the regression coefficients for ROA were -0.998, CR -0.021, and TATO 0.053. These three independent variables also had significance values ​​less than 0.05, indicating that they significantly influence firm value. Thus, the research results indicate that profitability and liquidity have a significant negative effect on firm value, while total asset turnover has a significant positive effect on firm value.